The evaluation of locally produced full-fat canola seed (Brassica napus) as an alternative protein source in the diets of slaughter ostriches (Struthio camelus var. domesticus) - Niemann, Gert Jacobus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.